2018
DOI: 10.1088/2053-1583/aaa574
|View full text |Cite
|
Sign up to set email alerts
|

Modified Brewster angle on conducting 2D materials

Abstract: Insertion of 2D materials in optical systems modifies their electrodynamical response. In particular, the Brewster angle undergoes an up-shift if a substrate is covered with a conducting 2D material. This work theoretically and experimentally investigates this effect related to the 2D induced current at the interface. The shift is predicted for all conducting 2D materials and tunability with respect to the Fermi level of graphene is evidenced. Analytical approximations for high and low 2D conductivities are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…On the contrary, the effect of graphene layer on top of SiO 2 is the shift of the pseudo‐Brewster angle to larger values in the visible range. [ 43,44 ]…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the effect of graphene layer on top of SiO 2 is the shift of the pseudo‐Brewster angle to larger values in the visible range. [ 43,44 ]…”
Section: Resultsmentioning
confidence: 99%
“…This expression also reproduces a previous result found by Majérus et.al. [10] in certain limiting case. Moreover, it is demonstrated that for σ xy = 0 the perfect suppression of the p-polarization reflectance is inhibited and, thus, the Brewster effect does not occur strictly.…”
Section: Discussionmentioning
confidence: 99%
“…[149][150][151] Majérus et al experimentally realized a Brewster angle shift in the ultraviolet-visible to near-infrared range by covering mono-, bi-, and trilayer graphene on the substrate, as shown in Figure 15B. 152 Chen et al showed an electrically tunable Brewster device in THz for the first time, in which the Brewster angle could be electrically tuned from 65 to 72 ( Figure 15C and D). 150 The Brewster device was operated as both an intensity and phase modulator.…”
Section: Optical Reflection Geometrymentioning
confidence: 99%
“…The tunable Brewster angle effect based on graphene has been demonstrated in different wavelength regions and also used in different optical devices 149‐151 . Majérus et al experimentally realized a Brewster angle shift in the ultraviolet‐visible to near‐infrared range by covering mono‐, bi‐, and trilayer graphene on the substrate, as shown in Figure 15B 152 . Chen et al showed an electrically tunable Brewster device in THz for the first time, in which the Brewster angle could be electrically tuned from 65° to 72° (Figure 15C and D).…”
Section: Optical Reflection Geometrymentioning
confidence: 99%
See 1 more Smart Citation